2020
DOI: 10.1038/s41598-020-73157-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoretic analysis of ligand-specific conformational states of the inhibitory glycine receptor embedded in copolymer nanodiscs

Abstract: The glycine receptor (GlyR), a member of the pentameric ligand-gated ion channel family (pLGIC), displays remarkable variations in the affinity and efficacy of the full agonist glycine and the partial agonist taurine depending on the cell system used. Despite detailed insights in the GlyR three-dimensional structure and activation mechanism, little is known about conformational rearrangements induced by these agonists. Here, we characterized the conformational states of the α1 GlyR upon binding of glycine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…A variety of methods have been developed to study the binding of ligands to macromolecules, including several that do not make use of labeled ligands, such as isothermal-titration calorimetry (e.g., Wöhri et al, 2013 ), surface plasmon resonance (e.g., Seeger et al, 2012 ), and microscale thermophoresis (e.g., Bernhard and Laube, 2020 ). One of the key advantages of methods that do use labeled ligands, however, is that the relationship between the observed signal and the ligand-binding phenomenon under study is most straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of methods have been developed to study the binding of ligands to macromolecules, including several that do not make use of labeled ligands, such as isothermal-titration calorimetry (e.g., Wöhri et al, 2013 ), surface plasmon resonance (e.g., Seeger et al, 2012 ), and microscale thermophoresis (e.g., Bernhard and Laube, 2020 ). One of the key advantages of methods that do use labeled ligands, however, is that the relationship between the observed signal and the ligand-binding phenomenon under study is most straightforward.…”
Section: Resultsmentioning
confidence: 99%
“…MST measurements showed that the full agonist glycine and the partial agonist taurine induced different conformational transitions on binding to the GlyR, giving EC50 values of 65 ± 22.8 µM and 473.8 ± 66.1 µM, respectively (Figure 4). The results indicated that partial agonism in pLGIC proteins is reflected by the adaption of distinct receptor conformations [49]. (a) Dose-response data for glycine and taurine of heterologous expressed α1 GlyR from Xenopus laevis oocytes.…”
Section: Other Receptorsmentioning
confidence: 99%
“…33 The different systems were chosen to investigate both the suitability of different lipid models to the application of MST and lipid-AMP binding, and the impact the choice of model system can have on the binding. SMA nanodiscs and vesicles were chosen as they have been previously utilised in MST, 23,34 and the effects of differences in surface curvature could be investigated. SMA-QA was selected as it possesses a cationic polymer belt, in contrast to SMA which has an anionic belt.…”
Section: Introductionmentioning
confidence: 99%